2021
DOI: 10.3390/ijms222111789
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Systemic Curcumin Administration Antagonizes Murine Sarcopenia and Presarcopenia

Abstract: Curcumin administration attenuates muscle disuse atrophy, but its effectiveness against aging-induced, selective loss of mass or force (presarcopenia or asthenia/dynopenia), or combined loss (sarcopenia), remains controversial. A new systemic curcumin treatment was developed and tested in 18-month-old C57BL6J and C57BL10ScSn male mice. The effects on survival, liver toxicity, loss of muscle mass and force, and satellite cell responsivity and commitment were evaluated after 6-month treatment. Although only 24-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 57 publications
1
24
0
Order By: Relevance
“…Furthermore, in older subjects, curcumin may promote the optimal microvascular perfusion of skeletal muscles [ 257 ]. Multiple studies conducted in animal models of sarcopenia have shown that oral administration of curcumin is associated with the reduction of muscle wasting and improvements in markers of inflammation and oxidative stress [ 258 , 259 ]. Similar effects were also obtained with parenteral administration [ 260 ].…”
Section: Interaction Between Phenolic Compounds and Microbiota: Possi...mentioning
confidence: 99%
“…Furthermore, in older subjects, curcumin may promote the optimal microvascular perfusion of skeletal muscles [ 257 ]. Multiple studies conducted in animal models of sarcopenia have shown that oral administration of curcumin is associated with the reduction of muscle wasting and improvements in markers of inflammation and oxidative stress [ 258 , 259 ]. Similar effects were also obtained with parenteral administration [ 260 ].…”
Section: Interaction Between Phenolic Compounds and Microbiota: Possi...mentioning
confidence: 99%
“…Curcumin supplementation also resulted in decreased muscle soreness (visual analogue scale (VAS) 2.88), when compared with placebo (VAS 3.36, p = 0.012). No differences were observed in TAC, TNF, or MDA [ 127 ]. In a study by Hillman et al the authors aimed to determine the effects of curcumin supplementation on delayed onset muscle soreness and muscle power following plyometric exercise.…”
Section: Nutraceuticals With Anti-inflammatory Properties and Their P...mentioning
confidence: 99%
“…Curcumin is also being associated with the prevention of age-related sarcopenia. Gorza et al [ 52 ] evaluated the effect of curcumin treatment at 120 µg/kg in a volume of 100 µL in 18-month-old C57BL6J and C57BL10ScSn male mice. In this study, the researchers observed that curcumin was able to significantly increase survival in both strains, preventing sarcopenia and pre-sarcopenia, preserving type-1 myofibers, and increasing type-2A ones, positively influencing the satellite cells by preserving adult levels of myofiber maturation in old, regenerating soleus muscle.…”
Section: Curcuminmentioning
confidence: 99%